Beth's speed was 60 mph.
<h3>
What is speed?</h3>
- The speed (commonly referred to as v) of an object in everyday use and kinematics is the magnitude of the change in its position over time or the magnitude of the change in its position per unit of time; it is thus a scalar quantity.
- The distance traveled by an object in a time interval is divided by the duration of the interval; the instantaneous speed is the limit of the average speed as the duration of the time interval approaches zero.
- Velocity is not the same as speed.
To find what was Beth's speed:
Beth's data:
- time = 2 hrs; rate = r mph; distance = r×t = 2r miles
Tim's data:
- time = 1 hr; rate = r-6 mph; distance = r-6 miles
Equation:
- distance + distance = 174 miles
So,
- 2r + r - 6 = 174
- 3r - 6 = 174
- 3r = 180
- r = 60 mph (Beth's rate)
- r-6 = 54 mph (Tims's rate)
Therefore, Beth's speed was 60 mph.
Know more about speed here:
brainly.com/question/4931057
#SPJ4
The sum of squares of numbers is: 13
Step-by-step explanation:
Let x and y be two numbers
Then,
Difference of the squares of the numbers will be:
![x^2-y^2](https://tex.z-dn.net/?f=x%5E2-y%5E2)
Product will be:
![xy](https://tex.z-dn.net/?f=xy)
Given identity is:
![(x^2+y^2)^2=(x^2-y^2)^2+(2xy)^2](https://tex.z-dn.net/?f=%28x%5E2%2By%5E2%29%5E2%3D%28x%5E2-y%5E2%29%5E2%2B%282xy%29%5E2)
Given values are:
Difference of the squares of the numbers=![x^2-y^2=5](https://tex.z-dn.net/?f=x%5E2-y%5E2%3D5)
Product of numbers = xy = 6
Putting the values in the identity
![(x^2+y^2)^2=(5)^2+[2(6)]^2\\=25+(12)^2\\=25+144\\=169](https://tex.z-dn.net/?f=%28x%5E2%2By%5E2%29%5E2%3D%285%29%5E2%2B%5B2%286%29%5D%5E2%5C%5C%3D25%2B%2812%29%5E2%5C%5C%3D25%2B144%5C%5C%3D169)
As we have to only find x^2+y^2
Taking square root on both sides
![\sqrt{(x^2+y^2)^2}=\sqrt{169}\\x^2+y^2=13](https://tex.z-dn.net/?f=%5Csqrt%7B%28x%5E2%2By%5E2%29%5E2%7D%3D%5Csqrt%7B169%7D%5C%5Cx%5E2%2By%5E2%3D13)
The sum of squares of numbers is: 13
Keywords: Identities
Learn more about identities at:
#LearnwithBrainly
in STR,
ST=SR
therefore, t=r(angles opposite equal sides of a triangle are equal)
T=73
C+73+73=180(ASP of triangle)
C=34
Answer:
Help me on my question please
Step-by-step explanation:
Solution:
we have been asked to find the product of (x+y+3)(x+y-4).
we will multiply term by term as below
![(x+y+3)(x+y-4)=x(x+y+3)+y(x+y+3)-4(x+y+3)\\\\\ (x+y+3)(x+y-4)=x^2+xy+3x+xy+y^2+3y-4x-4y-12\\\\\text{Now take the like terms together and simplify we get}\\\\(x+y+3)(x+y-4)=x^2+y^2+2xy-x-y-12\\](https://tex.z-dn.net/?f=%20%28x%2By%2B3%29%28x%2By-4%29%3Dx%28x%2By%2B3%29%2By%28x%2By%2B3%29-4%28x%2By%2B3%29%5C%5C%5C%5C%5C%20%28x%2By%2B3%29%28x%2By-4%29%3Dx%5E2%2Bxy%2B3x%2Bxy%2By%5E2%2B3y-4x-4y-12%5C%5C%5C%5C%5Ctext%7BNow%20take%20the%20like%20terms%20together%20and%20simplify%20we%20get%7D%5C%5C%5C%5C%28x%2By%2B3%29%28x%2By-4%29%3Dx%5E2%2By%5E2%2B2xy-x-y-12%5C%5C%20)
Hence the the product of (x+y+3)(x+y-4) is ![x^2+y^2+2xy-x-y-12](https://tex.z-dn.net/?f=%20x%5E2%2By%5E2%2B2xy-x-y-12%20)